A Comprehensive Review Analysis of the Effects of Social Media on the Tourism Industry - Dixit, Aprna (Journal of Advanced Research in Journalism & Mass Communication, 2022)
Information and Communication Technology (ICTs) have undergone rapid development over the past ten years, which has had significant effects on the global tourism industry. It is now widely acknowledged by researchers and sector professionals that social media significantly affects both suppliers and consumers in the tourism industry. This study’s purpose is to analyze the literature and conduct a critical analysis of papers that cover the impact of social media on the search and tourism industry. In purpose to perform this study, data were gathered from the three main databases: Google Scholar, Science Direct and EBSCO Host. The study was conducted in three stages: first, a database was chosen with the purpose of gathering data; second, the data was screened; and third, the study itself was carried out after the successful screening of the data. For the purpose of performing this study, a total of 28 papers that were pertinent to the study were discovered. Based on a review of the relevant literature from the viewpoints of both tourism consumers and suppliers, this article discovered that while consumers use social media before, during and after travel to look for different types of information, suppliers typically use it for promotion, communication, management and research.